Penguatan UMKM Desa Dukuhbenda Melalui Optimalisasi Kerajinan Tote Bag Ecoprint - Helsa Ardiansyah, Ilham; Surya Agung Lesmana; Lesa Paranti (Jurnal Bina Desa, 2025)
The purpose of community service is to empower MSMEs to make tote bag crafts using ecoprint techniques. The service method used is training with the target community of MSME actors in Dukuhbenda Village. The craft of making tote bags using ecoprint techniques is to be able to increase the diversification of MSME products that have added value so that it is hoped that it can increase sales turnover. This is also a place to show creativity in creating tote bag products. The results of the training showed high enthusiasm from the participants, increased skills, and the potential for developing a creative economy. With this program, it is hoped that sustainable solutions can be created to reduce plastic waste and increase community income. With the existence of products that have sales value, it can increase the entrepreneurial spirit of the community.